2024
DOI: 10.1200/op.23.00153
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Patient Health Insurance Coverage and Out-of-Pocket Costs for Genomic Testing in Oncologists' Treatment Decisions

K. Robin Yabroff,
Kewei Sylvia Shi,
Jingxuan Zhao
et al.

Abstract: PURPOSE Use of genomic testing, especially multimarker panels, is increasing in the United States. Not all tests and related treatments are covered by health insurance, which can result in substantial patient out-of-pocket (OOP) costs. Little is known about oncologists' treatment decisions with respect to patient insurance coverage and OOP costs for genomic testing. METHODS We identified 1,049 oncologists who used multimarker tumor panels from the 2017 National Survey of Precision Medicine in Cancer Treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…For example, in a survey of 1049 oncologists who reported using genomic testing, 47.3% and 32.7% reported that patient insurance coverage for genomic testing was very important and somewhat important, respectively, in treatment decisions. 25 In another study including 1220 oncologists who discussed genomic testing with patients, 50.0% reported often discussing the likely costs of testing and related treatments and 26.3% reported sometimes discussing costs. 26 However, ctDNA testing is already in the clinic and increasingly being used.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a survey of 1049 oncologists who reported using genomic testing, 47.3% and 32.7% reported that patient insurance coverage for genomic testing was very important and somewhat important, respectively, in treatment decisions. 25 In another study including 1220 oncologists who discussed genomic testing with patients, 50.0% reported often discussing the likely costs of testing and related treatments and 26.3% reported sometimes discussing costs. 26 However, ctDNA testing is already in the clinic and increasingly being used.…”
Section: Discussionmentioning
confidence: 99%